Determinants of the Internet Islamic Banking Services Adoption in Jordan - Alhawamdeh, Loai Naser Mahmoud; Bardai, Bardai (Universitas Islam Negeri Raden Intan Lampung, 2017)
Objective: The purpose of this study is to conceptually review the determinants of Internet Islamic Banking Services adoption.In addition, it presents a conceptual research model to understand these relationships supported by literature review from recent studies.Methodology:A critical literature review had been conducted in the area of internet banking services adoption model, Islamic banking and UTAUT theory and application. Results: The main findings indicate that familiarity, social influence, needs, customer background and IT support affect adoption of internet banking services. In addition familiarity, social influence, needs, customer background and IT support affect adoption of Islamic internet banking services .Therefore we can conclude that factors of internet banking services affect Islamic internet banking services. Implication: This researchpresents a conceptually yet empirically supported model to describe the factors influencing internet banking services and internet Islamic banking services. This research will be significant in several areas, by adding new knowledge for the academics, practitioners and organizations in general and particularly in JordanObjective: The purpose of this study is to conceptually review the determinants of Internet Islamic Banking Services adoption.In addition, it presents a conceptual research model to understand these relationships supported by literature review from recent studies.Methodology:A critical literature review had been conducted in the area of internet banking services adoption model, Islamic banking and UTAUT theory and application. Results: The main findings indicate that familiarity, social influence, needs, customer background and IT support affect adoption of internet banking services. In addition familiarity, social influence, needs, customer background and IT support affect adoption of Islamic internet banking services .Therefore we can conclude that factors of internet banking services affect Islamic internet banking services. Implication: This researchpresents a conceptually yet empirically supported model to describe the factors influencing internet banking services and internet Islamic banking services. This research will be significant in several areas, by adding new knowledge for the academics, practitioners and organizations in general and particularly in Jordan